Rhizospheric Fungal and Bacterial Bio-Agents in Flowering And Bulb of Tuberose (Polianthes Tuberosa L.) (Bangladesh Journal of Botany, 2022)
The present investigation was carried out to study the influence of rhizospheric fungal and bacterial bioagents on the flowering and bulb parameters of tuberose with eight treatments [Strain-A i.e. Aspergillus sp., Strain-P i.e. Penicillium sp., Strain-A + Agro-aquasorb (AS), Strain-P + Agro-aquasorb, Bacillus subtilis (BS) + Bacillus megeterium (BM), BS + AS, BM + AS along with control (AS)]. Among these treatments, treatment T4 i.e., Strain A+AS (Aspergillus sp.106 propagules/ml+ Agro-aquasorb 40 g/bulb) exhibited superiority for most of the parameters viz., floret diameter (4.83 cm), spike length (82.12 cm), number of spikes per m2 area (39.99), maximum number of florets per spike (51.87) and weight of spike (94.41g) whereas treatment T2 [Strain-A (Aspergillus sp.)] resulted in higher yield (316.06).Bangladesh J. Bot. 51(3): 565-572, 2022 (September)